The micro-foundations of permanent austerity: Income stagnation and the decline of taxability in advanced democracies - Olivier Jacques; David Weisstanner (Luxembourg Income Study (LIS), 2022)
The slowdown of economic growth and the stagnation of incomes for substantial parts of the population in recent decades are well-known. But what are the implications of these changes for the politics of taxation? The consensus in the literature is that income change either has no effect or that large income decline raises support for welfare policies. Focusing on the revenue side of the welfare state rather than the spending side, we present the opposite argument: We predict that economic decline makes individuals less tolerant of paying taxes, because tax increases would imply a reduction of their consumption level. We test this argument using longitudinal data from both repeated cross-sections and panel surveys in the United States, Canada and Japan. Our main finding is that tolerance of paying taxes is lower when individuals perceive that their economic situation deteriorates. Thus, perceived economic decline can create political obstacles against higher taxation.
Keywords: 330